Could chroman-4-one derivative be a better inhibitor of PTR1? – Reason for the identified disparity in its inhibitory potency in Trypanosoma brucei and Leishmania major. (February 2021) - Omolabi, Kehinde F.; Iwuchukwu, Emmanuel A.; Odeniran, Paul O.; Soliman, Mahmoud E.S.
Graphical abstract: Molecular visualizations of compound 1 interactions at the biopterin active site of [A] Tb PTR1 and [B] Lm PTR1. Selective inter-molecular interactions of the chroman-4-one moiety and non- chroman-4-one moiety with crucial active site residues in Tb PTR1 and Lm PTR1 is equally unveiled. Highlights: Compound 1 displayed higher binding free energy in Tb PTR1 than Lm PTR1. The orientation of compound 1 in Tb PTR1 and Lm PTR1 influenced its potency. Compound 1 induced structural rigidity in Tb PTR1 than in Lm PTR1. NADPH played a crucial role in the activity of compound 1 in Tb PTR1. Abstract: Most notable Kinetoplastids are of the genus Trypanosoma and Leishmania, affecting several millions of humans in Africa and Latin America. Current therapeutic options are limited by several drawbacks, hence the need to develop more efficacious inhibitors. An investigation to decipher the mechanism behind greater inhibitory potency of a chroman-4-one derivative (compound 1) in Trypanosoma brucei pteridine reductase 1 ( Tb PTR1) and Leishmania major pteridine reductase 1 ( Lm PTR1) was performed. Estimation of ΔGbind revealed that compound 1 had a greater binding affinity in Tb PTR1 with a ΔGbind value of −49.0507 Kcal/mol than −29.2292 Kcal/mol in Lm PTR1. The ΔGbind in Tb PTR1 were predominantly contributed by "strong" electrostatic energy compared to the "weak" van der Waals in Lm PTR1. In addition to this, the NADPH cofactor contributed significantly to the total energy of Tb PTR1. A characteristic weak aromatic π interaction common in PTR1 was more prominent in Tb PTR1 than Lm PTR1. The consistent occurrence of high-affinity conventional hydrogen bond interactions as well as a steady interaction of crucial active site residues like Arg14/Arg17, Ser95/Ser111, Phe97/Phe113 in Tb PTR1/ Lm PTR1 with chroman-4-one moiety equally revealed the important role the moiety played in the activity of compound 1. Overall, the structural and conformational analysis of the active site residues in Tb PTR1 revealed them to be more rigid than Lm PTR1. This could be the mechanism of interaction Tb PTR1 employs in exerting a greater potency than Lm PTR1. These findings will further give insight that will be assistive in modifying compound 1 for better potency and the design of novel inhibitors of PTR1.